COVID-19: Pre-Purchase Trust and Health Risk Impact on M-Commerce Experience – Young Customers Experience on Food Purchasing. Issue 3 (27th May 2022) - Suhartanto, Dwi; Kartikasari, Ani; Najib, Mukhamad; Leo, Gundur
Abstract: This study evaluates the impact of pre-purchase trust and health risk on young customer experience and satisfaction with online food purchasing during the COVID-19 pandemic, by integrating the valence theoretical framework and quality-based behavioral model. Using an online survey, data were gathered from 444 customers in the Indonesian region of Bandung. This study reveals that incorporating pre-purchase trust and health risks offers a new understanding of young customers' experience and satisfaction with online food purchasing. The result of this study suggests that the proposed integrated model provides a better understanding of young customer experience in purchasing food through mobile apps.